Little Miss Bossy - Hargreaves, Roger (Manchester World International Publishing Ltd., 1981)
Wilfred the Wizard cures Little Miss Bossy's problem with a wizardy word and a pair of magic boots.
Keywords: Behavior -- Fiction; Magic -- Fiction; Wizards -- Fiction